Drug delivery via α-Cyclodextrin: A Statistical-Nucleus Independent Chemical Shifts (S-NICS) study - Ghazimokri, Hediyeh Sadat; Monajjemi, Majid; Aghaie, Hossein (Revista de la Universidad del Zulia, 2020)
This study aims to investigate a novel method by using nucleus independent chemical shifts or S-NICS method of cyclo-dextrin. Monajjemi et.al (2008 a, 2015) has exhibited this novel method which so called “S-NICS” a few years ago. This program is arranged to calculate the aromaticities in some non-benzene rings. As the asymmetry (η) and skew (κ) parameters are fluctuated in a short and are alternative in lengthy distances, the S-NICS is a certain criterion for estimating the aromaticity. By generation of pseudo-random numbers in a Monte Carlo calculation which distributed in different function, the maximum abundant of skew and asymmetry parameters have been calculated for (η∗), (κ∗), and lastly the modified isotropy ( ) has been calculated for α-Cyclodextrin as an electromagnetic criterion. The results revealed that positive S-NICS and NICS values for α-Cyclodextrin indicate anti-aromaticity. It was observed from the values of (η∗), (κ∗) based on our calculations for α-Cyclodextrin is negatives which are depending on the distances to the center of those rings. At last, by this work it has been presented a schematic diagram of S-NICS for post-ab-initio calculations.